Dakwah in Youth Development of Karang Taruna in Kanjilo Village, Barombong Subdistrict, Gowa Regency - Mutmainna, Mutmainna; Tike, Arifuddin; Tajibu, Kamaluddin (Jurnal Mercusuar, 2021)
The main problem of this research is how preaching can be used in the development of youth through the Karang Taruna group in Kanjilo Village, Barombong Sub-District, Gowa Regency. The research used a descriptive qualitative method with a preaching approach, and the data sources were obtained directly from several youth members, as well as local village and security officials in Kanjilo Village, Barombong Sub-District, Gowa Regency. The results of this research show that: 1) The increase in creativity of Karang Taruna Tunirannuang in developing youth in Kanjilo Village, Barombong Sub-District, is grouped into various fields with productive activities. 2) The forms of youth development activities in Karang Taruna Tunirannuang in Kanjilo Village, Barombong Sub-District, Gowa Regency include spiritual guidance, physical development, and artistic development.